Virulence and Antibiotic Resistance Profiles of Cronobacter sakazakii and Enterobacter spp. Involved in the Diarrheic Hemorrhagic Outbreak in Mexico - Parra-Flores, Julio; Aguirre, Juan; Juneja, Vijay; Jackson, Emily E.; Cruz-Córdova, Ariadnna; Silva-Sanchez, Jesus; Forsythe, Stephen (Frontiers in Microbiology, 2018)
Cronobacter spp. are bacterial pathogens that cause neonatal meningitis, septicemia, and necrotizing enterocolitis in infants with a lethality rate of 40–80%. Powdered infant formulas (PIF) have been implicated as the main vehicles of transmission. This pathogen can also cause infection through contaminated expressed breast milk, and it has been recovered from neonatal feeding tubes of neonates not fed reconstituted PIF and milk kitchen areas. This study analyzed antibiotic resistance profiles and the tissue virulence tests of Cronobacter sakazakii and Enterobacter spp. recovered from PIF, infant fecal matter‘s, and milk kitchen environment involved in a diarrheic hemorrhagic outbreak in 2011 in Mexico. The strains isolated from the outbreak had similar antibiotic resistance profiles and pathogenicity irrespective of isolation site, however, C. sakazakii strains isolated from PIF showed significantly higher invasive profiles than Enterobacter spp. (p = 0.001) and 83% were resistant to more than one antibiotic. The findings of this study can be used to complement existing information to better control Cronobacter and Enterobacter spp. contamination in PIF production, prevent its transmission, and improve infant food safety.